Catastrophizing, pain and disability in patients with non-specific low back pain (2015)
Background: Attention has been drawn to examining the contributions of “catastrophising” to the prediction of pain and disability in individuals with low back pain (LBP). Objectives: This study investigated the proportion of patients with LBP who engaged in catastrophic thinking about pain and its association with pain intensity and disability. We also investigated the components of pain catastrophising that is predictive of disability. Methods: A total of 275 participants with nonspecific LBP completed the Pain Catastrophizing Scale, the quadruple visual analog scale, and the Revised Oswestry Disability Questionnaire (RODQ). The associations among pain intensity, disability, and catastrophising were investigated using t test. The components of catastrophising that best predicts disability were investigated using multiple linear regressions, and the level of significance was set at 0.05. Results: The majority (85.5%) of the participants had LBP for more than 6 weeks, with 45.5% of the participants having moderate disability and 52.7% being high catastrophisers. High catastrophisers to pain had a significantly higher rating of pain intensity (p < 0.001) and higher score on the RODQ than low catastrophisers to pain. The main components of catastrophising that predicts disability were magnification (p < 0.001) and rumination (p= 0.006). Conclusion: Clinicians should screen patients with nonspecific LBP for a heightened level of catastrophic thinking and endeavour to manage such when present.